Kuliner Berbasis Bahan Pangan Lokal pada Masyarakat di Desa Lawela Kecamatan Batauga Kabupaten Buton Selatan - Wa Ode Fitriani; La Ode Topo Jers (JURNAL KABANTI: Kerabat Antropologi, 2023)
This study aims to identify and describe culinary based on local food ingredients and culinary defense strategies based on local food ingredients in the Lawela Village, Batauga District, South Buton Regency community. This research uses the Goodenough Cognitive System theory. The research method used a qualitative descriptive method with data collection carried out through observation and in-depth interviews. The results showed that: (1) local foodstuffs in Lawela Village such as corn, cassava, sweet potato, and taro can produce local culinary; (2) The Community Strategy in maintaining Culinary Based on Local Food Ingredients in Lawela Village is to be preserved and developed.